Modulating AtDREB1C Expression Improves Drought Tolerance in Salvia miltiorrhiza - Wei, Tao; Deng, Kejun; Zhang, Qingxia; Gao, Yonghong; Liu, Yu; Yang, Meiling; Zhang, Lipeng; Zheng, Xuelian; Wang, Chunguo; Liu, Zhiwei; Chen, Chengbin; Zhang, Yong (Frontiers in Plant Science, 2017)
Dehydration responsive element binding proteins (DREB) are transcription factors of the plant-specific AP2 family, many of which contribute to abiotic stress responses in several plant species. We investigated the possibility of increasing drought tolerance in the traditional Chinese medicinal herb, Salvia miltiorrhiza, through modulating the transcriptional regulation of AtDREB1C in transgenic plants under the control of a constitutive (35S) or drought-inducible (RD29A) promoter. AtDREB1C transgenic S. miltiorrhiza plants showed increased survival under severe drought conditions compared to the non-transgenic wild-type (WT) control. However, transgenic plants with constitutive overexpression of AtDREB1C showed considerable dwarfing relative to WT. Physiological tests suggested that the higher chlorophyll content, photosynthetic capacity, and superoxide dismutase, peroxidase, and catalase activity in the transgenic plants enhanced plant drought stress resistance compared to WT. Transcriptome analysis of S. miltiorrhiza following drought stress identified a number of DEGs between the AtDREB1C transgenic lines and WT. These DEGs are involved in photosynthesis, plant hormone signal transduction, phenylpropanoid biosynthesis, ribosome, starch and sucrose metabolism, and other metabolic pathways. The modified pathways involved in plant hormone signaling are thought to be one of the main causes of the increased drought tolerance of AtDREB1C transgenic S. miltiorrhiza plants.